Damage caused by Tetranychus Merganser Bondreaux (Acari: Tetranychidae) on Nopal Verdura Opuntia Ficus-Indica (L.) Miller during winter - J. Lima-Espíndola; J.M. Vanegas-Rico (Journal of Entomological and Acarological Research, 2017)
The spider mite Tetranychus merganser occurs in some crops in Mexico and USA. This mite could be considered a potential pest in countries like Japan. In this work we recorded the damages that T. merganser causes to the nopal verdura (prickly pear vegetable crop) in one of the principal cactus crop regions of Mexico.